2014
DOI: 10.1021/jf504035s
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Study Reveals a Co-occurrence of Gallic Acid-Induced Apoptosis and Glycolysis in B16F10 Melanoma Cells

Abstract: Gallic acid (GA) has long been associated with a wide range of biological activities. In this study, its antitumor effect against B16F10 melanoma cells was demonstrated by MTT assay, cell migration assay, wound-healing assay, and flow cytometric analysis. GA with a concentration >200 μM shows apoptotic activity toward B16F10 cells. According to Western blotting data, overexpressions of cleaved forms of caspase-9, caspase-3, and PARP-1 and pro-apoptotic Bax and Bad, accompanied by underexpressed anti-apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Gallic acid has been shown to induce apoptosis in cancer cells and it has been recognized as a chemopreventive agent [33,35,36]. However, there is no study in the literature supporting the possible mechanism of action of neolignans, cedrusin ( 2 ), and balanophonin ( 3 ), in the induction of human cancer cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Gallic acid has been shown to induce apoptosis in cancer cells and it has been recognized as a chemopreventive agent [33,35,36]. However, there is no study in the literature supporting the possible mechanism of action of neolignans, cedrusin ( 2 ), and balanophonin ( 3 ), in the induction of human cancer cell death.…”
Section: Resultsmentioning
confidence: 99%
“…In murine B16F10 melanoma cells, this compound is described for inducing apoptosis through the mitochondrial pathways by promoting the overexpression of the enzymes caspase-3, caspase-9 and PARP-1 as well as the pro-apoptotic proteins Bax and Bad; it also promotes the under-expression of the anti-apoptotic proteins Bcl-2 and Bcl-xL [85]. In human melanoma cells (A375.S2), in addition to the involvement of caspases and pro- and anti-apoptotic proteins, an increase in ROS production and a decrease in mitochondrial membrane potential are observed [86].…”
Section: Discussionmentioning
confidence: 99%
“…Although the PP extract was less effective than the EL and WP extracts, it reduced the cell viability by 46% at a concentration of 500 μg/mL. The poten- [Liu et al, 2014], probably due to the complex prooxidant action of gallate compounds [Badhani et al, 2015]. A proteomic approach revealed that the gallic acid-induced cellular apoptosis in these cells is associated with metabolic glycolysis.…”
Section: Cytotoxic Effects Of the Aqueous Extracts On B16f10 Cellsmentioning
confidence: 98%